(3cJGH TGed dLejY GdLhGfH GdfXQjI hGdJWHjbjIs - (3gGTe ahRj OHGS(B, (3GdYHGOjs ((3YeGf(B:s (3OGQ GdhQGb ddfTQ(B,s, 2008)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3adSaI GdgfOSI GdeGdjI h VQhQJgG,eaGgje eJYdbI HGdgfOSI GdeGdjI,COhGJ GdgfOSI GdeGdjI h CfhGYgG, ahGFO COhGJ GdgfOSI GdeGdjI h eNGWQ GdJWHjb GdNGWF dgG,GdNjGQGJ GdeGdjI,eaGgje eJYdbI HGdNjGQGJ GdeGdjI, feGPL JSYjQ GdNjGQGJ, ESJQGJjLjI GdeVGQHI aj GdNjGQGJ GdeGdjI,ESJQGJjLjI GdESJKeGQ aj GdNjGQGJ GdeGdjI,ESJQGJjLjI GdJMhW ddNjGQGJ GdeGdjI, GdNjGQGJ GdeGdjI eG Hjf GdfXQjI h GdJWHjbs
(3HjHdjhZQGajG U(B.302s
Keywords: (3GdGOGQI GdeGdjIs; (3GdGbJUGO GdeGdjs; (3GdeGdjI YGeIs; (3GdgfOSI GdeGdjIs